Models, systems, networks in economics, engineering, nature and society - S.V. Chuprov; A.V. Babkin (Модели, системы, сети в экономике, технике, природе и обществе)
Background. With the increasing digitalization of the Russian economy, understanding the dominant trends in the distribution and protection of information flows in a non-stationary space is gaining theoretical and practical significance. An evolving industrial system immersed in such environments is characterized by highly disturbed processes and metamorphoses displayed by nonlinear phenomena, measures of chaos and order of its behavior. On this basis, taking into account the discussed phenomena, the article is aimed at analyzing and ensuring the stability of the industrial system in the face of the impact of both flows of technological and product innovations of the digitalized economy and geopolitical and economic threats that aggravate the behavior of the system. Materials and methods. The theoretical and methodological basis of the study was formed by the doctrines of thermodynamics, statistical physics, nonlinear dynamics, concepts and methods of theories catastrophe, communication and information, cybernetics and synergetics, evolutionary and innovative economics and production management. Results. Using their ideas and analytics, the concepts of entropy, chaos and the effect of the functioning of the system supported by the control information coming into it are revealed. Within the framework of information theory, the influence of signal and noise parameters on information processes in the economy, the features of their transmission and distortion are characterized. In the context of the statistical dependence of the effect of the economic system's activity on the control information accumulated in it, the transformation and interpretation of this exponential dependence with measures of the order of behavior of the industrial system are performed. Nonlinear phenomena of this dependence and the evolution of the industrial system are interpreted in order to achieve its stable effect. Conclusions. The study complements theoretical ideas about the factors ensuring the stability of the functioning of modernized industrial systems and argues for the need for a symbiosis of natural and economic sciences to deepen the analysis and interpretation of the phenomena of the evolution of chaotic industrial systems in a digitalized economy.